The Influence Of The Implementation Of Zakat Management Policy On The Management Of The Zakat Amil Agency In Orderly Administration And The Effectiveness Of Reporting And Accountability Of Zakat Management In The Zakat Amil Agency Of West Java Province - Abdal (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract This research aims to analyze the influence of the implementation of zakat management policies on the management of the Amil Zakat Agency in orderly administration and the effectiveness of reporting and accountability for zakat management at the Amil Zakat Agency of West Java Province. The research method used in this research is descriptive analysis method with survey techniques. The data collection techniques used are documentation studies and field studies including questionnaires, interviews and observations. The data analysis technique used to answer the research hypothesis is a statistical analysis technique using the path analysis model. Keywords: Accountability, orderlyadministration, Reporting, Accountability, Zakat